HUMOR IS NECESSARY FOR INTENSIFICATION LEARNING CREATIVE TECHNOLOGIES IN ENGINEERING EDUCATION - Valeriy Likholetov; Sergei Aliukov (Universitas Diponegoro, 2021)
The article reveals the possibilities of using joke and cartoon as didactic tools that are adequate to the goals of